Les valeurs de la nature dans les iles subantarctiques - Anne Atlan (Éditions en environnement VertigO, 2019)
This article explores the values attributed to nature and how they are articulated in a particular territory, the French sub-Antarctic islands. Since these islands do not have permanent populations and are not exploited for their biological or mining resources, the values directly utilitarian are not present there, and the other types of values are expressed more widely than in more classical situations. By conducting sociological surveys of the residents of Kerguelen and on board the Marion Dufresne, we were able to draw up a typology of the values expressed and how they were assigned by the individuals. Most of the values identified are plural, such as values of authenticity, affective, spiritual, or science-related values, and are expressed in different ways. However, we did not observe any significant variations based on social categorizations such as age, gender or occupational status. We have distinguished the « value-principle » from the « values-object », that is, the different attributes of nature that are endowed with value. We were then able to study the modes of adherence to these values, which can be shared or cleavant, and compare them with their legitimacy to justify the principles of action.